The market economy and Christian ethics - Sedgwick, P. (New studies in Christian ethics, 1999)
Peter Sedgwick explores the relation of a theology of justice to that of human identity in the context of the market economy, and engages with critics of capitalism and the market. He examines three aspects of the market economy: first, how does it shape personal identity, through consumption and the experience of paid employment in relation to the work ethic? Second, what impact does the global economy have on local cultures? Finally, as manufacturing changes out of all recognition through the impact of technology and global competition, what is the effect in terms of poverty? Drawing on the response of the Catholic Church, both in the United States and in papal encyclicals, to the market economy from 1985–1991, Sedgwick argues that its involvement deserves to be better known. Moreover, he recommends that the Churches remain part of the debate in reforming and humanizing the market economy.